Analisis Legalitas Tanah Wakaf Muhammadiyah Jawa Tengah dengan menggunakan Algoritma ID3 - Muhammad Munsarif (Elkom : Jurnal Elektronika dan Komputer, 2020)
Waqf information system In April 2020 shows the number of waqf land in Indonesia has an area of ​​51,259.84 Ha. More waqf received in the form of land creates a problem of disputes and disputes that lead to legal cases Muhammadiyah is the second-largest Islamic organization that has assets in the form of waqf land that has not been able to resolve existing problems. In this study, an analysis of legal potential and waqf land disputes is used using ID3 Algorithm to classify potential land disputes based on the status of the land deed, owner's name, location of waqf and its use so that it can produce data on the ownership rights of waqf land which has the potential for legal disputes and no legal disputes. research shows that potential legal problems are still present. The ID3 algorithm is able to produce information as a basis for reducing disputes and the loss of waqf land.